THE TRANSFORMATION OF FERGANA REGION INTO A RAW MATERIAL BASE OF THE RUSSIAN EMPIRE (SECOND HALF OF THE 19TH CENTURY) (Scientific journal of the Fergana State University, 2025)
The article discusses the transformation of Fergana region into a raw material base by the Russian Empire in the second half of the 19th century, based on the materials of the national and St. Petersburg archives and other historical sources, and the measures taken for the development of cotton production.